2011
DOI: 10.1590/s0100-69912011000200011
|View full text |Cite
|
Sign up to set email alerts
|

Cicatrização da parede abdominal após hepatectomia parcial

Abstract: OBJETIVO: Avaliar a cicatrização da ferida incisional da parede abdominal de ratos hepatectomizados quanto à concentração de colágeno, reação inflamatória e angiogênese. MÉTODOS: Utilizaram-se 48 ratos distribuídos aleatoriamente para laparotomia com e sem hepatectomia. As cicatrizes foram estudadas no 3º, 7º e 14º dia de pós-operatório. Analisou-se a densidade do colágeno por método histoquímico e a angiogênese por método imunohistoquímico. RESULTADOS: A análise do colágeno total mostrou menor concentração no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In an experimental review by Biondo-Simões et al, it was shown that the procedure of hepatectomy leads to a delay of the healing process, interfering with collagen synthesis and angiogenesis, which could explain the results of incisional hernia, but not addressing type of incision [20].…”
Section: Discussionmentioning
confidence: 99%
“…In an experimental review by Biondo-Simões et al, it was shown that the procedure of hepatectomy leads to a delay of the healing process, interfering with collagen synthesis and angiogenesis, which could explain the results of incisional hernia, but not addressing type of incision [20].…”
Section: Discussionmentioning
confidence: 99%
“…The animals were housed in the Laboratory of the Discipline of Surgical Technique and Experimental Surgery of the Federal University of Paraná, where they remained during the quarantine period and throughout the experiment. The sample size was calculated based on previous works with a similar research protocol approved by CEUA-BIO 18 , 19 .…”
Section: Methodsmentioning
confidence: 99%